2003
DOI: 10.4049/jimmunol.171.7.3485
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Preconceptional Immunization for Protective and Nonpathological Specific Immunity in Murine Neonates

Abstract: Expression of Th2 immunity against environmental Ags is the hallmark of the allergic phenotype and contrasts with the Th1-like pattern, which is stably expressed in healthy adults throughout life. Epidemiological studies indicate that the prenatal environment plays an important and decisive role in the development of allergy later in life. Since the underlying mechanisms were unclear, an animal model was developed to study the impact of maternal allergy on the development of an allergic immune response in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
111
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 40 publications
8
111
0
2
Order By: Relevance
“…A large percentage of the OVA-sensitized groups developed skin hypersensitivity reactions consistent with a higher response to allergic stimuli (Herz et al, 2001). Similar findings were reported by Uthoff et al (2003), however in their study development of an IgE response against the same allergen was completely prevented early in life. This effect was mediated by diaplacental transfer of allergen-specific IgG 1 antibodies (Abs).…”
Section: Allergen Modelssupporting
confidence: 76%
See 1 more Smart Citation
“…A large percentage of the OVA-sensitized groups developed skin hypersensitivity reactions consistent with a higher response to allergic stimuli (Herz et al, 2001). Similar findings were reported by Uthoff et al (2003), however in their study development of an IgE response against the same allergen was completely prevented early in life. This effect was mediated by diaplacental transfer of allergen-specific IgG 1 antibodies (Abs).…”
Section: Allergen Modelssupporting
confidence: 76%
“…The contradictory data may be explained by differences in the timing and mode of maternal exposure to allergens, and by considering evidence obtained by Uthoff et al (2003) and others that transplacental transfer of IgE but not IgG is minimal, and that transfer of allergen generally freely occurs. In a recent paper, Matson et al (2007) showed that the conditions surrounding allergy in the mother during gestation can influence the development of tolerance to that antigen later in life.…”
Section: Allergen Modelsmentioning
confidence: 99%
“…Interestingly, when high IgG1-antibody levels were found in the offspring, the generation of codfish-specific IgEantibodies was significantly suppressed. This phenomenon has already been observed previously (29,30). A possible explanation is that maternal IgG1 can function as blocking antibodies via formation of immune complexes, which then attach to the FcγRII-receptor and the B-cell receptor on B-cells, generating negative intracellular signals by crossaggregation of these receptors (30,31).…”
Section: Discussionmentioning
confidence: 78%
“…However, previous murine studies support our observations: There is a preventive effect of a specific sensitization of the mother against the respective antigen in the offspring via IgG-antibodies. At the same time, other factors transported from the mother may be responsible for a broad Th2-response toward multiple heterologous antigens in the newborns (28,30,31). The present study shows for the first time that the same effects can be achieved by the oral route when sucralfate is taken.…”
mentioning
confidence: 99%
“…This model thus excludes a critical role for transplacental passage of the allergen itself or allergen-specific immunoglobulins produced by the mother. 11,12 In fact, because treatment of asthmatic females with anti-IL-4 monoclonal antibodies before mating significantly ameliorated the offspring susceptibility to asthma, 9 our results point to a prominent role for maternal Th2 cytokines. Because T lymphocytes can provide the Th2 cytokines that both induce allergic inflammation and alter the lung function of asthmatics, 13 we postulated that allergen-specific T cells are sufficient, in our model, to mediate the maternal transfer of asthma risk.…”
mentioning
confidence: 75%